Ultrasound-Responsive Smart Drug Delivery System of Lipid Coated Mesoporous Silica Nanoparticles - Muhammad Umair Amin; Sajid Ali; Imran Tariq; Muhammad Yasir Ali; Shashank Reddy Pinnapreddy; Eduard Preis; Christian Wölk; Richard D. Harvey; Gerd Hause; Jana Brüßler; Udo Bakowsky (MDPI AG, 2021)
The immediate release of chemotherapeutics at the target site, along with no premature release in circulation is always challenging. The purpose of this study was to develop a stimuli responsive drug delivery system, composed of lipid supported mesoporous silica nanoparticles (MSNPs) for triggered drug release at the target site and simultaneously avoiding the premature release. MSNPs with a higher drug loading capacity and very slow release were designed so as to enhance release by FDA approved US-irradiation. Doxorubicin, as a model drug, and perfluoropentane (PFP) as a US responsive material, were entrapped in the porous structure of MSNPs. Lipid coating enhanced the cellular uptake and in addition provided a gatekeeping effect at the pore opening to reduce premature release. The mechanical and thermal effects of US induced the conversion of liquid PFP to a gaseous form that was able to rupture the lipid layer, resulting in triggered drug release. The prolonged stability profile and non-toxic behavior made them suitable candidate for the delivery of anticancer drugs. This smart system, with the abilities of better cellular uptake and higher cytotoxic effects on US-irradiation, would be a good addition to the applied side of chemotherapeutic advanced drug delivery systems.